2020
DOI: 10.1002/jmv.26729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum hepatic enzyme activities in different COVID‐19 phenotypes

Abstract: Coronavirus disease 2019 (COVID‐19) is a newly emerging infectious disease. Our understanding of the clinical characteristics of liver damage and the relationship with disease severity in COVID‐19 is still limited. To investigate the serum hepatic enzyme activities in different phenotypes of COVID‐19 patients, evaluate their relationship with the illness severity and analyze the correlation of glycyrrhizin treatment and abnormal liver enzyme activities, one hundred and forty‐seven patients with COVID‐19 were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Additionally, the extent of bilirubin in non-survivors had shown significantly increased levels. In similar studies, an increase in total bilirubin has been reported in patients with severe COVID-19 [31,32]. In our study, the amount of albumin has decreased in the non-survivors, which was similar to the results of an investigation by Huang et al, who reported that serum albumin level <35 g/L at presentation increased the risk of death in COVID-19 by at least 6-fold [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the extent of bilirubin in non-survivors had shown significantly increased levels. In similar studies, an increase in total bilirubin has been reported in patients with severe COVID-19 [31,32]. In our study, the amount of albumin has decreased in the non-survivors, which was similar to the results of an investigation by Huang et al, who reported that serum albumin level <35 g/L at presentation increased the risk of death in COVID-19 by at least 6-fold [28].…”
Section: Discussionsupporting
confidence: 91%
“…The liver impairment in COVID-19 is not a prominent feature; however, the mechanism and importance of elevated ALP and total Bilirubin must be considered in the association of prognosis. Accordingly, numerous cases of changes in liver enzymes have been reported in patients with COVID-19, including increased ALT, AST, LDH, Y-Gammaglutamyl Transferase (GGT), Superoxide Dismutase (SOD), ALP, and total Bilirubin [31,32]. We found that ALP levels were higher in nonsurvivor.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have shown that coinfection with HBV and other viruses can lead to rapid progression of liver disease and an increased risk of death [ 7 ]. In addition, COVID-19 also causes abnormal liver function and liver damage [ 8 ]. However, the results of previous studies are inconsistent on whether COVID-19 and HBV coinfection will increase the risk of death and critical illness [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients had also increased serum LDH levels and decreased SOD levels. However, treatment with diammonium glycyrrhizinate preparation alleviated the abnormal liver enzyme activities in non-critical COVID-19 patients [189]. It's another preparation Diammonium glycyrrhizinate has shown to reduce acute liver injury in patients with COVID-19 [190].…”
Section: Liver Diseasementioning
confidence: 99%